DAMPAK PANDEMI COVID-19 TERHADAP PEREKONOMIAN MAKRO JAWA TIMUR - Silfia Yulianawati; Moeheriono; Sri Hartati Setyowarni (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2022)
East Java has natural resources and human resources that can support economic growth. This research is interesting because East Java Province has the highest number of Covid-19 cases in Indonesia in June 2020. The purpose of this research is to find out and analyze the impact of the Covid- 19 pandemic on the macro economy of East Java, especially on GDP, inflation, and unemployment in East Java. The approach used in this research is descriptive using qualitative research methods. The data used in this study are primary and secondary data. The results of this study are the Covid-19 pandemic has an impact on the macro economy of East Java. As a result of the outbreak of the pandemic, this has resulted in impacts including a contraction in PDRB, an increase in the number of unemployed and inflation. The business fields that are very depressed due to the Covid- 19 pandemic are the hotel and restaurant sector in the service sector and footwear in the manufacturing sector. With this impact, the government made several efforts to minimize the impact on the economy. The efforts made by the government are sufficient to minimize the impact and restore the East Java economy.